2019
DOI: 10.1121/1.5116009
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive factors contribute to speech perception in cochlear-implant users and age-matched normal-hearing listeners under vocoded conditions

Abstract: This study examined the contribution of perceptual and cognitive factors to speech-perception abilities in cochlear-implant (CI) users. Thirty CI users were tested on word intelligibility in sentences with and without semantic context, presented in quiet and in noise. Performance was compared with measures of spectral-ripple detection and discrimination, thought to reflect peripheral processing, as well as with cognitive measures of working memory and non-verbal intelligence. Thirty age-matched and thirty youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 83 publications
3
43
0
Order By: Relevance
“…The observed correlation between the WASI Perceptual Reasoning Index and overall serial span ability is similar to the previously observed correlations between short-term memory and general fluid intelligence latent constructs (Gignac & Weiss, 2015;Unsworth & Engle, 2007a). There was a nonsignificant trend relating the WASI Perceptual Reasoning Index to sentence recognition, which had approximately the same effect size as previously reported relationships between other tests of fluid intelligence and vocoded speech (O'Neill et al, 2019). Previous research has found weak correlations between speech recognition and various cognitive subscales (Dryden et al, 2017), which may reflect the general association between fluid intelligence and speech recognition.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The observed correlation between the WASI Perceptual Reasoning Index and overall serial span ability is similar to the previously observed correlations between short-term memory and general fluid intelligence latent constructs (Gignac & Weiss, 2015;Unsworth & Engle, 2007a). There was a nonsignificant trend relating the WASI Perceptual Reasoning Index to sentence recognition, which had approximately the same effect size as previously reported relationships between other tests of fluid intelligence and vocoded speech (O'Neill et al, 2019). Previous research has found weak correlations between speech recognition and various cognitive subscales (Dryden et al, 2017), which may reflect the general association between fluid intelligence and speech recognition.…”
Section: Discussionsupporting
confidence: 72%
“…This relationship is most evident in listeners with hearing loss, who often struggle with speech recognition even if they use hearing aids or cochlear implants. Listeners with hearing loss often differ from listeners with typical hearing in their relationships between speech recognition and various measures of cognition, such as fluid intelligence, memory, and attention ( Kaandorp et al, 2017 ; Kronenberger et al, 2014 ; Moberly, Harris, et al, 2017 ; Moberly et al, 2016 ; Moberly, Houston, et al, 2017 ; O'Neill et al, 2019 ; G. N. Smith et al, 2019 ). Currently, it is unclear how to interpret these differences across groups of listeners.…”
mentioning
confidence: 99%
“…Thus, although responses to these two surprisal measures cannot be directly compared, the stronger tracking of surprisal by older adults in our study is consistent with increased reliance on predictive processes in this population. This is in agreement with behavioral results demonstrating greater reliance on semantic context in populations with compromised representations of speech, such as those with hearing loss (Benichov et al, 2012;Lash et al, 2013) and cochlear implants (Amichetti et al, 2018;Dingemanse and Goedegebure, 2019;O'Neill et al, 2019). Importantly, the seemingly conflicting pattern of results between these studies could in fact reflect two distinct contributors to speech perception difficulties in older adults, namely decreases in the fidelity of lower level representations, and cognitive decline.…”
Section: Relationship To Existing Work On Age-effects On Electrophysisupporting
confidence: 86%
“…Specifically, a key compensatory mechanism for the poorer fidelity of peripheral representation in the aging population may be increased reliance on the successfully identified segments of speech to aid inference about speech segments with lower SNR. Indeed, greater dependence on contextual cues for speech comprehension has been demonstrated in populations with compromised representations of speech, including those with hearing loss ( Benichov et al, 2012 ; Lash et al, 2013 ) and cochlear implants ( Amichetti et al, 2018 ; Dingemanse and Goedegebure, 2019 ; O’Neill et al, 2019 ). In the context of our feature-tracking model, a possible manifestation of heightened reliance on predictive processes would be increased tracking of surprisal.…”
Section: Discussionmentioning
confidence: 99%